Pelagic seabirds as biomonitors of persistent organic pollutants in the Southwestern Atlantic - Quadri Adrogué, Agustina; Miglioranza, Karina Silvia Beatriz; Copello, Sofía; Favero, Marco; Seco Pon, Juan Pablo (Marine Pollution Bulletin)
Persistent Organic Pollutants (POPs) are accumulated through time and can exert different effect on ecosystems. POPs and Chlorpyrifos, a current use pesticide, were assessed in body feathers of males and females of Black-browed albatross (Thalassarche melanophris, BBA) and Cape petrels (Daption capense, CAP) during their non-breeding seasons at the Patagonian Shelf, Argentina. Chlorpyrifos showed the highest values among all pollutants in both species (49.56–84.88 ng g−1), resulting from current agricultural practices. The pattern OCPs > PCBs > PBDEs was observed in both species, and CAP showed higher concentrations than BBA probably as a consequence of higher lipid mobilization and pollutants availability during dispersion. Non-significant differences between sexes about POPs levels were found; however a slight tendency was observed, females>males in CAP, and males>females in BBA. More attention and further studies are needed to understand seabirds' physiology and its relationship with the pollutants distribution in their tissues and considering breeding season. Fil: Quadri Adrogué, Agustina. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias Marinas. Laboratorio de Ecotoxicología; Argentina Fil: Miglioranza, Karina Silvia Beatriz. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias Marinas. Laboratorio de Ecotoxicología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Copello, Sofía. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Departamento de Biología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. ...